The Influence of Work Period and Work Motivation on Asn's Interest in Continuing Studies: JEL Classification: J24; J28; M54; I26; H83 - Andi Magfirah. A; A. Nur Insan; M. Nasir Hamzah (Newinera Publisher, 2025)
Civil servants' interest in continuing their studies to a higher level of education poses a unique challenge amid efforts to improve the capacity and professionalism of the civil service. This study was conducted to analyze and explain the influence of length of service and work motivation on civil servants' interest in continuing their studies, both partially and simultaneously. This study uses an explanatory quantitative approach with multiple linear regression analysis techniques. The study employs a census technique with a population of 73 civil servants working at the Department of Women's Empowerment, Child Protection, Population Control, and Family Planning of South Sulawesi Province. The analysis results indicate that length of service has a positive and significant influence on civil servants' interest in continuing their education. This reflects that the longer someone works, the higher the potential desire to enhance their competencies through formal education. Additionally, work motivation also has a positive and significant influence on the interest in continuing education, indicating that internal drives such as the desire to achieve, grow, and attain higher career positions further strengthen civil servants' decisions to pursue further education. Simultaneously, length of service and work motivation were found to have a significant impact on civil servants' interest in continuing their education. These findings indicate that extensive work experience and high levels of motivation can be important driving factors in increasing civil servants' interest in pursuing further education as part of their personal and professional development.